Comparison of coronary artery dimensions in patients with chronic aortic regurgitation or stenosis - Hamza Sunman; Mehmet Erat; Kadriye Gayretli Yayla; Engin Algül; Mehmet Aytürk; Lale Dinç Asarcıklı; Murat Bilgin; Tolga Çimen; Ahmet Akyel; Sadık Açıkel; Mehmet Doğan; Ekrem Yeter (KARE Publishing, 2016)
Objective: Effects of various conditions on coronary artery dimensions is an important research topic, and data regarding effect of aortic valvular diseases are limited. Aim of the present study was to investigate effects of aortic regurgitation (AR) and aortic stenosis (AS) on coronary artery dimensions. Methods: Coronary dimensions of 95 patients (35 with isolated AR, 30 with isolated AS, and 30 without any valvular disease) were calculated. Patients with severe coronary artery disease and concurrent moderate to severe additional valvular disease were excluded. Mean diameter of major coronary arteries was determined using quantitative coronary angiography. Results: The 3 study groups were similar in terms of baseline characteristics. Diameter of left main coronary artery was found to be greater in AR group than AS group (2.66+-0.57 mm/m2 vs 2.36+-0.49 mm/m2; p=0.015). Mean diameter of left anterior descending and left circumflex arteries were found to be similar in AR and AS groups, and greater than control group. Mean diameter of right coronary artery was found to be greater in AR group compared with controls; however, no significant difference was found in same measurement between AS group and controls. Conclusion: Present study findings indicate that coronary dimensions in AR group tend to be greater than AS group. Further studies investigating factors that affect coronary dimensions would be beneficial in order to demonstrate mechanisms and differences in AR and AS groups.